Fen Bilimleri Dersinde Tamamlayıcı Ölçme ve Değerlendirme Yaklaşımlarından Portfolyo Kullanımının Akademik Başarı ve Kalıcılığa Etkisinin Araştırılması - Saylan, Aslı; Yanar, Sinan; Kaya, Hasan (Muş Alparslan Üniversitesi, 2019)
The study aimed to investigate the effects of portfolio teaching methodin science on 6th grade students'achievement and permanence of learning.Pre-test and post-test control group experimental design was used. Whileexperimental group was taught through portfolio teaching; control group wastaught through discussion, question-and-answer, and expository teaching. Thestudy group consisted of 60 students attending a middle school in Kayseriduring 2016-2017 academic year. In the study that Light and Sound AcademicAchievement Test (LSAAT) prepared by researchers was used, both post-test andretention test scores was found significantly higher than pre-test scoreswhereas no significant difference was found between post-test and retention testscores. Additionally, experimental group’s post-test and retention test scoreswere significantly higher than control group. Accordingly, portfolio method hada large effect on post-test scores, and a moderate effect on retention testscores.

Çalışmanın amacı, fen bilimlerinde portfolyo öğretim yönteminin 6. sınıföğrencilerinin başarıları ve öğrenmenin kalıcılığı üzerindeki etkilerininincelenmesidir. Ön test-son test kontrol gruplu yarı deneysel deseninkullanıldığı araştırmada konular deney grubunda portfolyo öğretim yöntemiyle, kontrol grubunda sunuş, soru-cevap ve tartışma yöntemleriyle işlenmiştir.Çalışma grubunu 2016-2017 öğretim yılında Kayseri’deki bir ortaokulda öğrenimgörmekte olan 60 öğrenci oluşturmaktadır. Araştırmacılar tarafından hazırlananIşık ve Ses Akademik Başarı Testi’nin (ISABT) kullanıldığı çalışmada, öğrencilerin son test ve kalıcılık testi puanları ön test puanlarından anlamlıderecede yüksek bulunurken, son test ve kalıcılık testi puanları arasında farkbulunmamıştır. Ayrıca deney grubunun son test ve kalıcılık testi puanlarıkontrol grubundan anlamlı derecede yüksektir. Dolayısıyla, portfolyo yöntemison test puanları üzerindeki büyük, kalıcılık testi puanları üzerinde ise ortadüzeyde etkilidir.
Investigation of the Effects of Using Portfolio as an Alternative Assessment and Evaluation Approach on Students'Academic Achievement and Permanence of Learning in Science Course
anemon
Keywords: Portfolio-based teaching; science education; academic achievement; Portfolyo ile öğretim; fen bilimleri eğitimi; akademik başarı